Efektivitas Pembelajaran Coding Aplikasi Scratchjr terhadap Kecerdasan Linguistik Anak Usia 5-6 Tahun - Annisa Fitri; Nelly Marhayati; Irwan Satria (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aims to examine the effectiveness of coding instruction using the ScratchJr application in enhancing the linguistic intelligence of children aged 5–6 years at PAUD Pajar Harapan. The study employed a quantitative experimental approach using a One-Group Pretest–Posttest Design. The research sample consisted of 17 children in Group B selected through a total sampling technique. Data were collected using an observation checklist designed to assess children's ability to identify English vocabulary, name objects in English, and recognize pictures based on the teacher's verbal instructions. The collected data were analyzed using descriptive and inferential statistics, including the normality test, homogeneity test, and paired-samples t-test. The findings revealed a substantial improvement in children's linguistic performance, with the mean pretest score increasing from 28.82 to 68.23 in the posttest. Hypothesis testing yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference in children's linguistic intelligence before and after participating in ScratchJr-based coding instruction. The learning activities, which involved arranging programming blocks, creating simple animations, and presenting digital stories, provided interactive learning experiences that encouraged children to communicate, expand their English vocabulary, and express ideas with greater confidence. These findings demonstrate that coding instruction using the ScratchJr application is effective in enhancing the linguistic intelligence of children aged 5–6 years at PAUD Pajar Harapan.